Functional subcellular distribution of β1‐ and β2‐adrenergic receptors in rat ventricular cardiac myocytes. Issue 3 (22nd August 2013) - Cros, Caroline; Brette, Fabien
Abstract β‐adrenergic stimulation is a key regulator of cardiac function. The localization of major cardiac adrenergic receptors (β1 and β2) has been investigated using biochemical and biophysical approaches and has led to contradictory results. This study investigates the functional subcellular localization of β1‐ and β2‐adrenergic receptors in rat ventricular myocytes using a physiological approach. Ventricular myocytes were isolated from the hearts of rat and detubulated using formamide. Physiological cardiac function was measured as Ca2+ transient using Fura‐2‐AM and cell shortening. Selective activation of β1‐ and β2‐adrenergic receptors was induced with isoproterenol (0.1 μmol/L) and ICI‐118, 551 (0.1 μmol/L); and with salbutamol (10 μmol/L) and atenolol (1 μmol/L), respectively. β1‐ and β2‐adrenergic stimulations induced a significant increase in Ca2+ transient amplitude and cell shortening in intact rat ventricular myocytes (i.e., surface sarcolemma and t‐tubules) and in detubulated cells (depleted from t‐tubules, surface sarcolemma only). Both β1‐ and β2‐adrenergic receptors stimulation caused a greater effect on Ca2+ transient and cell shortening in detubulated myocytes than in control myocytes. Quantitative analysis indicates that β1‐adrenergic stimulation is ~3 times more effective at surface sarcolemma compared to t‐tubules, whereas β2‐ adrenergic stimulation occurs almost exclusively at surface sarcolemma (~100 times more effective). These physiological data demonstrate that in rat ventricular myocytes, β1‐adrenergic receptors are functionally present at surface sarcolemma and t‐tubules, while β2‐adrenergic receptors stimulation occurs only at surface sarcolemma of cardiac cells.